Nutritional Value of Silkworm Pupae (Bombyx mori) with Emphases on Fatty Acids Profile and Their Potential Applications for Humans and Animals - Mihaela Hăbeanu; Anca Gheorghe; Teodor Mihalcea (Insects, 2023)
Bombyx mori is an ideal lepidopteran species representative of many scientific studies, a model of studies for medicine and a significant insect from an ecological standpoint. This review was performed to summarize the fatty acids (FA) composition of silkworm pupae (SP) that are associated with other important compounds that could add value to SP, diversifying the ways of valorization. The proposal to complete plant-based feeds with insect-based feeds represents a viable option to beneficially impact human and animal health and the environment. The quality and quantity of fats consumed significantly impact the aetiology of certain diseases. The key compounds of fat named essential FA (EFA) substantially influence the prevention and treatment of several diseases through their nutraceutical functions. Due to its excellent profile in nutrients such as protein and fat, amino acids and fatty acids composition, SP has become an important alternative feed ingredient and source of EFA. SP is a by-product that was discarded in large quantities. Following the need to act to improve human health and reduce climate change impact, many researchers focused on studying SP applications in the medical and agricultural industries. Several authors noticed an improvement in the health markers by using SP. The feed cost for the animal was reduced with economic implications. Minimization of environmental impact was recorded. Few precautions were recommended regarding SP use, although they should not be ignored. The composition of SP and its potential for use in various industries provides us with persuasive arguments for continuing to develop the sericulture industry.